Media Concentration: A Critical Political Economy Perspective - Manfred Knoche (tripleC: Communication, Capitalism & Critique)
This article presents foundations of the analysis of media concentration from the perspective of the approach the critique of the political economy of the media and communication. It outlines the dangers and problems of media concentration, discusses the question of how to measure media concentration, identifies different types of media concentration, and gives a systematic overview of empirical studies of media concentration. As a result of the country comparison on a theoretical (macro) level with an analytically required high level of abstraction, first and foremost identities, commonalities and similarities with regard to the development of media concentration including its causes and consequences can be recognised. The author argues that media concentration also needs to be theorised. The paper distinguishes and discusses two such theoretical approaches: apologetic-normative competition theories of media concentration and critical-empirical theories of media concentration. Critical-empirical theories of media concentration situate media concentration in the context of the development of capitalism, which requires to use the critique of the political economy as theoretical foundation.